The Impact of Inaccurate Visual Representation of Tourism on Tourist Perception: Case Study Braga Street, Bandung - Nurrul Fadilah Dwiyanti, Nurrul Fadilah Dwiyanti; Fadillah Nur Islami, Fadillah Nur Islami; Ricky Hermayanto, Ricky Hermayanto; Alfadiya Rizki Oksavira, Alfadiya Rizki Oksavira; Aini Nurhasanah, Aini Nurhasanah; Azamat Abdullayev, Azamat Abdullayev (Journal of Tourism and Creativity, 2025)
Visual marketing is frequently employed in tourism marketing to attract public interest and encourage visits to specific destinations. However, there are instances where photos displayed, such as on social media, differ from the actual conditions. This study aims to investigate how misleading photos on social media influence tourists' intentions to spread negative word of mouth. These photos, which do not reflect reality, often trigger various negative reactions, such as anger, distrust, and regret among visitors after experiencing the destination. This research adopts a quantitative approach to examine the relationships among these variables. The study was conducted in the Jalan Braga tourist area in Bandung, involving 150 local university students who had visited the area as respondents. Regression analysis results indicate that negative emotions caused by misleading photos significantly impact respondents’ intentions to share negative reviews with others. These findings hold important implications for destination managers in managing destination images through online marketing strategies.